Impact of nitrogen fertilizer sustainability on corn crop yield: the role of beneficial microbial inoculation interactions - Fernando Shintate Galindo; Paulo Humberto Pagliari; Edson Cabral da Silva; Bruno Horschut de Lima; Guilherme Carlos Fernandes; Cassio Carlette Thiengo; João Victor Silva Bernardes; Arshad Jalal; Carlos Eduardo Silva Oliveira; Lucila de Sousa Vilela; Enes Furlani Junior; Thiago Assis Rodrigues Nogueira; et al. (BMC Plant Biology, 2024)
Abstract Background Considering the challenges posed by nitrogen (N) pollution and its impact on food security and sustainability, it is crucial to develop management techniques that optimize N fertilization in croplands. Our research intended to explore the potential benefits of co-inoculation with Azospirillum brasilense and Bacillus subtilis combined with N application rates on corn plants. The study focused on evaluating corn photosynthesis-related parameters, oxidative stress assay, and physiological nutrient use parameters. Focus was placed on the eventual improved capacity of plants to recover N from applied fertilizers (AFR) and enhance N use efficiency (NUE) during photosynthesis. The two-year field trial involved four seed inoculation treatments (control, A. brasilense, B. subtilis, and A. brasilense + B. subtilis) and five N application rates (0 to 240 kg N ha−1, applied as side-dress). Results Our results suggested that the combined effects of microbial consortia and adequate N-application rates played a crucial role in N-recovery; enhanced NUE; increased N accumulation, leaf chlorophyll index (LCI), and shoot and root growth; consequently improving corn grain yield. The integration of inoculation and adequate N rates upregulated CO2 uptake and assimilation, transpiration, and water use efficiency, while downregulated oxidative stress. Conclusions The results indicated that the optimum N application rate could be reduced from 240 to 175 kg N ha−1 while increasing corn yield by 5.2%. Furthermore, our findings suggest that replacing 240 by 175 kg N ha−1 of N fertilizer (-65 kg N ha−1) with microbial consortia would reduce CO2 emission by 682.5 kg CO2  −e ha−1. Excessive N application, mainly with the presence of beneficial bacteria, can disrupt N-balance in the plant, alter soil and bacteria levels, and ultimately affect plant growth and yield. Hence, highlighting the importance of adequate N management to maximize the benefits of inoculation in agriculture and to counteract N loss from agricultural systems intensification.